2008
DOI: 10.1021/es8022495
|View full text |Cite
|
Sign up to set email alerts
|

Ferric Oxide Mediated Formation of PCDD/Fs from 2-Monochlorophenol

Abstract: The copper oxide, surface-mediated formation of polychlorinated dibenzop-dioxins and dibenzofurans (PCDD/F) from precursors such as chlorinated phenols is considered to be a major source of PCDD/F emissions from combustion sources. In spite of being present at 2–50x higher concentrations than copper oxide, virtually no studies of the iron oxide-mediated formation of PCDD/F have been reported in the literature. We have performed packed bed, flow reactor studies of the reaction of 50 ppm gas phase 2-monochloroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 47 publications
3
51
0
Order By: Relevance
“…The reaction involves the attachment of the precursor on the surface of the catalytic matrix on the fly ash (Briois et al, 2007). The catalyzers are typically the transition metals such as Cu and Fe, which are present in fly ash and APCDs (Lomnicki and Dellinger, 2003;Nganai et al, 2008). Transitional-metals, especially copper, have been shown to enhance the formation of PCDD/Fs (Luijk et al, 1994;Ryu et al, 2005;Liao et al, 2016).…”
Section: Formation and Decomposition Mechanisms Of Pcdd/fsmentioning
confidence: 99%
“…The reaction involves the attachment of the precursor on the surface of the catalytic matrix on the fly ash (Briois et al, 2007). The catalyzers are typically the transition metals such as Cu and Fe, which are present in fly ash and APCDs (Lomnicki and Dellinger, 2003;Nganai et al, 2008). Transitional-metals, especially copper, have been shown to enhance the formation of PCDD/Fs (Luijk et al, 1994;Ryu et al, 2005;Liao et al, 2016).…”
Section: Formation and Decomposition Mechanisms Of Pcdd/fsmentioning
confidence: 99%
“…Iron chlorides and oxides stimulated the formation of chlorinated organic compounds in several model systems (Hoffman et al 1990;Nganai et al 2009;Ryan and Altwicker 2004). Moreover, Fe 2 O 3 catalyses the dimerisation of gas-phase precursors adsorbed onto the surface of a carbon matrix (Nganai et al 2009;Gullett et al 1990). …”
Section: Introductionmentioning
confidence: 99%
“…In principle, high Al, Fe, K, Pb and Ca concentrations found in the WB dust samples might be because: 1. fluxes, iron ore fines and coke breeze used in the iron ore sintering process could contain a variety of impurities, including Al 2 O 3 , and K 2 O (Cieplik et al, 2003;Nakano et al, 2005;Sammut et al, 2010); 2. the use of limestone (CaCO 3 ) and dolomite (CaMg(CO 3 )) as fluxes in the sintering process (Cieplik et al, 2003); and 3. the return fine used in the sintering process usually contains Pb compounds (Sammut et al, 2010). Among these five metal contents, several studies have shown that the existence of Fe and K might lead to the increase in PCDD/Fs formation (Hinton and Lane, 1991;Nganai et al, 2009;Fujimori et al, 2009). To the contrary, the existence of Pb (chloride and oxide) and Ca (oxide) might inhibit the formation of PCDD/Fs (Qian et al, 2005;Fujimori et al, 2009).…”
Section: Ionic Constituents Containing In Wb Dustsmentioning
confidence: 99%